2022
DOI: 10.3390/ijms23031022
|View full text |Cite
|
Sign up to set email alerts
|

ZIP8-Mediated Intestinal Dysbiosis Impairs Pulmonary Host Defense against Bacterial Pneumonia

Abstract: Pneumococcal pneumonia is a leading cause of morbidity and mortality worldwide. An increased susceptibility is due, in part, to compromised immune function. Zinc is required for proper immune function, and an insufficient dietary intake increases the risk of pneumonia. Our group was the first to reveal that the Zn transporter, ZIP8, is required for host defense. Furthermore, the gut microbiota that is essential for lung immunity is adversely impacted by a commonly occurring defective ZIP8 allele in humans. Tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Influenza, a primary respiratory infection, may cause digestive tract manifestations through hematogenous dissemination of infected lymphocytes from the respiratory tract [ 88 ]; and a decreased Bacteroides/Firmicutes ratio in the GI tract has been observed during RSV respiratory tract infection [ 89 ]. On the other hand, gut dysbiosis has been associated with both decreased levels of butyrate and exacerbated bacterial pneumonia, which supports the critical role of SCFAs in pulmonary host defense [ 90 ] and increases susceptibility to infections [ 91 , 92 ].…”
Section: Human Microbiome and Its Importance In Health And Diseasementioning
confidence: 87%
“…Influenza, a primary respiratory infection, may cause digestive tract manifestations through hematogenous dissemination of infected lymphocytes from the respiratory tract [ 88 ]; and a decreased Bacteroides/Firmicutes ratio in the GI tract has been observed during RSV respiratory tract infection [ 89 ]. On the other hand, gut dysbiosis has been associated with both decreased levels of butyrate and exacerbated bacterial pneumonia, which supports the critical role of SCFAs in pulmonary host defense [ 90 ] and increases susceptibility to infections [ 91 , 92 ].…”
Section: Human Microbiome and Its Importance In Health And Diseasementioning
confidence: 87%
“…For SCFAs, a validated UPLC-MS/MS was also used to evaluate samples ( Samuelson et al, 2022 ). In total, eight SCFAs were quantitated.…”
Section: Methodsmentioning
confidence: 99%
“…These changes were likewise associated with distinct patterns of mucin production (upregulated in male and down-regulated in female mice), which may explain the observed differential effects on the composition of the intestinal microbiota ( Kable et al, 2020 ). Finally, our group has recently demonstrated that myeloid-specific Zip8KO mice exhibit marked differences in the cecal microbial communities when compared to WT mice ( Samuelson et al, 2022 ). Specifically, we found that the loss of ZIP8 expression in myeloid lineage cells resulted in significant differences in beta-diversity and specific bacterial taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Precisely, we found that bacteria from the genuses Desulfovibrio and Intestinimonas , as well as the families Clostridiales Family_XIII and Lachnospiraceae, were enriched in WT mice compared to Zip8KO mice. Conversely, bacteria from the genuses Muribaculum , Erysipelatoclostridium , Mucispirillum , Parasutterella , and Prevotellaceae _UCG-001 , as well as from the family Ruminococcaceae were enriched in Zip8KO mice compared to WT mice ( Samuelson et al, 2022 ). Most strikingly, upon a S. pneumoniae lung infection, mice recolonized with Zip8KO-derived microbiota exhibited an increase in weight loss, bacterial dissemination, and lung inflammation compared to mice recolonized with WT microbiota ( Samuelson et al, 2022 ), which suggest that impaired Zn uptake not only influences the gastrointestinal microbiota, but that these changes also significantly influence host immune regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation